A drop in the circulating concentrations of soluble receptor for advanced glycation end products is associated with seroconversion to autoantibody positivity but not with subsequent progression to clinical disease in children en route to type 1 diabetes. Issue 4 (23rd January 2017) - Salonen, K.M.; Ryhänen, S.J.; Forbes, J.M.; Härkönen, T.; Ilonen, J.; Simell, O.; Veijola, R.; Groop, P.‐H.; Knip, M.
Abstract: Background: Advanced glycation end products (AGEs) and their interaction with the receptor for AGEs (RAGE) have been studied for their role in the pathogenesis and complications of type 1 diabetes. Decreased concentrations of soluble RAGE (sRAGE) have been reported in acute autoimmune inflammation. We set out to analyze the changes in sRAGE concentration during preclinical diabetes in children seroconverting to islet autoantibody positivity. Methods: We measured serum concentrations of sRAGE in 168 children who progressed to clinical disease and 43 children who turned positive for at least 2 diabetes‐associated autoantibodies but remained nondiabetic. We analyzed the sRAGE before seroconversion in the first autoantibody‐positive sample and annually thereafter until the diagnosis of type 1 diabetes or end of follow‐up. Results: Both groups had similar sRAGE before seroconversion, but subsequently, sRAGE concentrations were lower ( P  < .001) in the progressors. The progressors had significantly higher sRAGE concentrations before than after seroconversion ( P  < .001). The nonprogressors did not experience a similar decrease. The sRAGE concentrations remained stable after seroconversion in both groups. Conclusions: These data indicate that sRAGE may be involved in the initiation of beta‐cell autoimmunity but not in the progression from beta‐cell autoimmunity to clinical disease.